ASSESMENT OF ROCKFALL DITCH EFFECTIVENES BY APPLICATION OF COMPUTER SIMULATIONS, AN PROBABILISTIC APPROACH (Geologica Macedonica, 2022)
Different types of geohazards frequently affect road and railway traffic. Among them, in the case of mountainous terrains, the rockfalls are considered to be most usual. They cause economic losses of different magni-tude, in some cases even loss of human life. In order to improve the management of the rockfall hazard and risk, researchers had been developing many different methodologies for assesment and design of effective control, protection and preparedness measures. One of the approaches is to apply a structural measure along the road/railway line in the form of a rockfall catch ditch at the toe of the rock cuts. Experimental field tests and computer simulations by many authors have investigated the effectiveness of these ditches, with main goal being to design ditches that are as effective as possible. The paper presents application of computer simulation technique coupled with probabilistic analysis. The main idea is to test the effectiveness of rockfall catch ditches with different geometries, by simulating rockfall blocks of different geometrical shapes. Beside variation of the ditch and block geometry, also varied are the height and slope angle of the rock cut. Results from the probabilistic simulations show the different degree of ditch effectiveness in the investigated cases. The approach is considered useful for the goals in the design process, with main benefits being the improved management of the rockfall risk and economical rationalization of cuts design.
Keywords: geohazards; rockfalls; catch ditch; geometry; simulation; design rationalization